Special requirements for fishermen in the Nile River, Dakahlia governorate - Ibrahim, Eman Mohammed Mohammed; Afasha, Mona Hafez Mohammed Kamel Hafez (Journal of agricultural, environmental and veterinary sciences, 2022)
The following research aimed to identify the most important requirements of fishermen in the Nile River in Dakahlia Governorate. This research was conducted in the selected centers of the studied governorate. The data of this research were collected using a questionnaire method by personal interview for a simple random sample of fishermen in the Nile River, whose number reached 291 fishermen, representing about 24.3% of the studied centers during January 2021. Frequencies, percentages, relative weight, and correlation coefficient were used as tools for statistical analysis and to extract research results the most important results of this research are summarized as follows: About 85.6% of the sample are individuals who have a high level of total knowledge of hunting methods and laws, and the results indicate that mor than three quarters of the respondents 76.6% of the sample individuals have a high level of overall operational need for fishing methods and laws. The requirements related to social security ranked first with a relative weight of 81.10, followed by requirements related to financing, with a relative weight of 80.9, and the control requirements on the Nile River occupied the third order with a relative weight of 76.58.and, the results indicate that the relative importance of the services provided by the bodies of the Nile River was ranked in descending order as follows: Services related to water bodies' police, services related to fishermen's associations, services related to the Ministry of Environment, services related to the Public Authority for Fish Resources, with a relative weight of 70.69, 57.96,54.23 and 45.33, respectively, and the results indicate that the main reasons for the decline in fish productivity in the Nile are due to the continuous cleansing of dredges. Especially after the dumping of seed in the Nile River, the decrease in the quantity of seed in the fish river due to the lack of fish hatcheries. Contamination of the waters of the Nile River with sewage water, which leads to suffocation of seed, at rates of 100%, 91.1% and 89.7%, respectively.
Keywords: requirements; fishermen; the Nile River